The Effect of Pedagogic Competency and Family Environment Towards Students Entrepreneur Character in Madrasah Aliyah Negeri (MAN) 1 Pekanbaru - Nurhidayati, Nurhidayati; Sumarno, Sumarno; Kartikowati, Sri (Program Pascasarjana, Universitas Riau, 2018)
This study was aimed to determine the effect of (1) pedagogic competence on entrepreneurship character of MAN 1 Pekanbaru students, (2) family environment to entrepreneurship character of MAN 1 Pekanbaru students, and (3) jointly pedagogic competence and family environment on student entrepreneurship character MAN 1 Pekanbaru. This research is descriptive research with quantitative approach. The population in this study was 118 students in MAN 1 Pekanbaru academic year 2017-2018, with a sample of 91 students. Sampling using Probability Sampling technique with simple random sampling type. Data collection techniques used is questionnaires. The prerequisite analysis test includes normality test, linearity test, multicolinearity test, and heteroscedasticity test. Data analysis technique with F test and T test.The result of this research shows that (1) there are positive and significant influence of Pedagogic Competence on Entrepreneurship Character of MAN 1 Pekanbaru students with t arithmetic (1,718) bigger than t table that is (1,671) and significance value less than 0,05 0,002, by 41.80%. (2) there is positive and significant influence of Family Environment on Student Entrepreneurship Character MAN 1 Pekanbaru with t count (1,767) bigger than t table (1,671) and its significance value less than 0,05 0.000, while its influence equal to 56,80% and together (3) there is a positive and significant influence Pedagogic and Family Environment Competence on Student Entrepreneur Character MAN 1 Pekanbaru with F arithmetic (15,530) is bigger than F table (3,110) and its significance value smaller than 0,05 i.e. 0,000 . The major contribution of Pedagogical and Family Environment Competencies simultaneously on Entrepreneurship Character is 24.4%.